Handbook of energy efficiency and renewable energy - Handbook of energy efficiency and renewable energy (CRC, 2016)
Revised edition of: Handbook of energy efficiency and renewable energy / edited by Frank Kreith, D. Yogi Goswami. 2007; Includes bibliographical references and index